Effective strategy implementation conceptualizing firms? strategy implementation capabilities and assessing their impact on firm performance - Huber, Adele J. (Springer eBooks., 2011)
Adele J. Huber discovers that a firm's strategy implementation capabilities are a key driver of the strategies' performance outcomes. Drawing on organizational learning theory, she identifies the organizational abilities and processes that constitute a firm's Strategy Implementation Capability construct and shows empirically that the concept is very valuable in explaining how innovative strategies translate into a firm's performance. Her findings are particularly interesting for managers and researchers who focus on strategy formulation and execution. They also show the relation between strategy implementation and competitive advantage.